Political Aspects of Shari’a Banking Law in Indonesia - Djawahir Hejazziey (JURNAL INDO-ISLAMIKA, 2012)
This article discusses the history of the establishment of Islamic banking in Indonesia. The author examines the derivers of their establishment and argues that, aside other aspects, political aspects give contribution to the establishment of the Islamic banking. He describes a number of evidences of how politics play an important role in the success of their establishment; one of those proofs is the economic and political Islam interdependence which can be read in the idea of ​​Indonesian Muslims on establishing Islamic banks, which is influenced by political content. At the beginning, the relationship between Muslims and the New Order was covered with suspicions and prejudices. The rulers of the New Order in the 1970's were still suspicious of the idea on the establishment of an Islamic state or the realization of the Jakarta Charter. Until recent days, the idea is still debated.